The gut microbiota composition is shaped by disease activity and individual treatment responses in patients with multiple sclerosis - Ticha, Veronika; Coufal, Stepan; Jiraskova Zakostelska, Zuzana; Thon, Tomas; Roubalova, Radka; Hrncir, Tomas; Kverka, Miloslav; Pavelcova, Miluse; Kleinova, Pavlina; Lizrova Preiningerova, Jana; Kovarova, Ivana; Kreisinger, Jakub; et al. (Frontiers in Immunology, 2026)
Multiple sclerosis (MS) is a chronic autoimmune disorder of the central nervous system, with both animal and human studies highlighting a pivotal role for the gut microbiota in its pathogenesis. In this cross-sectional study, we investigated the potential role of gut microbiota in treatment response by analyzing its composition using 16S rRNA sequencing in treatment-naïve patients and those receiving disease-modifying therapies (interferon-beta (IFN-β), fingolimod, or cladribine), compared to healthy controls (HC). We also analyzed differences in gut microbiota composition and the serum levels of biomarkers associated with microbial translocation and inflammation based on treatment response. We found that individuals with clinically isolated syndrome (CIS) and treatment non-responders (NR) had significantly different alpha and beta diversity compared to HC. This effect was present in both IFN-β and fingolimod treatment. Individuals treated with cladribine had significantly different alpha and beta diversity regardless of the treatment outcome. The main differences in abundances in CIS and NR were found in bacteria that produce short-chain fatty acids. These patients also had significantly higher levels of lipopolysaccharide-binding protein and mannose-binding lectin compared to HC suggesting the compromised gut barrier function in multiple sclerosis leading to higher level of microbial translocation in these patients. In summary, we found that the treatment influences gut microbiota. Similar profile of gut microbiota and higher levels of molecules associated with microbial translocation were observed in patients with active disease (CIS and NR), suggesting the higher permeability of their gut barrier leading to pro-inflammatory tunning of their immune system.